Hydroinformatic tools and their potential in the search for missing persons in rivers. (December 2022) - Gonzalez, Jordi R. Palacios; Escobar-Vargas, Jorge; Vargas-Luna, Andrés; Castiblanco, Sergio; Trujillo, David; Guatame, Ana C.; Corzo, Gerald; Santos, Germán; Perez, Luz A.
Abstract: This research proposes a methodological approach to search floating bodies or floating body parts in rivers using hydroinformatic tools. These tools may allow possible search locations and potential release sites to be determined. The approach draws from hydrometric field information, two-dimensional (2D) hydrodynamic modeling, particle tracking (PT) models, and large-scale particle image velocimetry (LSPIV). This methodology was applied to a case study of the La Miel river in Colombia, where existing reports of deceased persons are available. A series of hydraulic accidents have been defined to represent the hydrodynamic and transport processes that occur in such situations. The results indicate that potential search locations, namely places where human floating bodies or floating body parts may be found, are principally on the left and right shores of recirculation systems.